Sistem Rekomendasi Paket Diskon Barang dengan Algoritma Apriori di Toko Ryzy - Widdy Arfiansyah; Iwan Rizal Setiawan; Prajoko Prajoko (STEKOM PRESS, 2022)
Discount is a sales strategy that lowers the price offered to buyers in the hope of increasing sales profits. However, when offering these discounts, stores often don't think about how discounted products can attract customers, so a support system is needed that can respond to the right and appropriate discounts. This support system with data mining techniques using apriori algorithm. This apriori method can search for several products that are often purchased simultaneously, therefore when juxtaposed with this study the effectiveness of the recommendations will be very good. Not only that, if it is added with a combination of recommendations with discounts, it will make customers interested to buying the product. The expected result of this research is to obtain a new sales strategy by making recommendations on items that will be used as discount packages.